Guidance on Healthy Eating Habits from the Medical Student’s Perspective - Rossi, Talita Cardoso; Bruno, Vânia Hercilia Talarico; Catarucci, Fernanda Martin; Beteto, Ivan Da Silva; Habimorad, Pedro Henrique Leonetti; Patrício, Karina Pavão (Associação Brasileira de Educação Médica, 2019)
ABSTRACT Although nutrition is one of the most significant aspects of good health and well-being, preventing many diseases and reducing premature death and disability, most medical curricula still do not cover this topic in depth, devoting only a few hours to it. This leaves an important gap in the training of medical professionals, in a context of an increase in chronic diseases, where healthy eating is essential, not only for prevention but also to guarantee treatment success. The present study interviewed medical students from the first to the sixth years of graduation, in order to understand what they consider to be a healthy diet and whether they consider themselves capable of guiding their future patients in the adoption and practice healthy eating habits. This is a qualitative study in which semi-structured interviews were conducted with 28 undergraduate medical students of a public university in the state of São Paulo. The data were analyzed using the technique of Content Analysis, with a thematic representational approach. Two major themes emerged, showing possible gaps in the students’ knowledge about nutrition and the difficulty they have in helping their patients switch to healthier eating habits, given that they themselves have difficulty doing the same. There is a need for medical schools to promote students’ health, both physical and mental, in response to the high demands of the courses. This may include health promotion activities aimed at the students themselves, encouraging them to adopt healthier lifestyles, especially healthier eating habits, so that they can share their own experiences with future patients. This may benefit their professional practice, giving them greater confidence when giving nutrition guidance to their patients, as they will have already experienced and applied the principles in their own lives. Patient-centered care can be a way to address this system and help patients effectively switch to healthier habits, thereby reducing suffering and improving quality of life. Empowerment through activities that receive and support the student and the patient is an essential tool for behavioral change.

RESUMO The rising number of students leagues in the Escola Paulista de Medicina of the Universidade Federal de São Paulo (EPM–Unifesp) leads to questions about their meaning to students and their role in medical training, as well as concerns about learning distortions, early specialization, social relevance, and insertion in the Brazilian national health system, called the Sistema Único de Saúde (SUS). In order to try and clarify these questions, this qualitative study analyzes the statues of the leagues, and the statements of tutors and students, gathered by means of four focal groups with students and two interviews with the tutors. We found 45 leagues currently running at the EPM–Unifesp, most of them associated with a medical specialty. The main motivators for joining in a league were: the search for practical activities, the desire to gain more experience of a particular specialty, the desire for more knowledge, and the need to be recognized as a responsible adult. Of the leagues studied, few conducted research or university extension activities, focusing on treatment and theoretical classes, supervised by professors, non-teacher physicians, resident doctors, or more senior students. The tutors are in charge of the organizational aspects. The leagues can reproduce graduation models, such as an overburdoning with activities and poor expository classes. Concerning insertion in the SUS, the leagues could be a means of training future SUS professionals. Although students claim that they intend to specialize in the league’s field, the tutors disagree that they lead to early specialization. We consider that while leagues fill gaps in the learning and expectations of the course, they are limited in regards to the impact of their activities on medical training and their social relevance. They can subvert the curricular structure and favor early specialization. We recommend that universities pay closer attention to students leagues, observing their number, selection process, activities, tutors involved and explicit objectives, with the purpose of evaluating their roles in the curriculum and medical training.
Orientação de Hábitos Alimentares Saudáveis sob o Olhar do Estudante de Medicina
Keywords: Medical Education; Curriculum; Nutritional Sciences; Healthy Diet; Educação Médica; Currículo; Ciências da Nutrição; Dieta Saudável